Developing a controller of two-wheeled self-balancing robot by using Arduino microcontroller / Saiful Amirul Asyraf Mohd Halid ... [et al.] - Mohd Halid, Saiful Amirul Asyraf; Mohd Noor, Nurul Muthmainnah; Ahmad, Farrah Noor; Yusof, Yaa’kob (2020)
Most of two-wheeled self-balancing robot is designed based on an inverted pendulum system, which is thedynamically system stable but not for steadily system. The objective of this project is to design the simple self-balancing robot using SOLIDWORKS software, then this robot will be controlled by using Android application via Arduino interface as a microcontroller. The idea of this project was used a sensor which called as IMU to estimate and obtain the tilt angle of the robot. To make the better performance in term of balancing and stability, a PID concept was applied to correct the error between the desired set point and the actual tilt angle position. The error was calculated to adjust the motor speed accordingly for the balancing and stability of robot. The robot system also was implemented with Android and Arduino microcontroller to move from one place to another place. As the results, the robot was able to balance the system acceptably but with some limitations due of noisy and disturbance of environment. In addition, the PID tuning using heuristic method was used to find and improve the balancing and stability of the robot system.